CHARACTERISTICS OF HYBRID BROADCAST BROADBAND TELEVISION (HBBTV) - Jakšić, Branimir; Milošević, Ivana; Petrović, Mile; Ilić, Siniša; Bojanić, Slobodan; Vasić, Selena (Bulletin of Natural Sciences Research, 2017)
This paper describes the working principle of hybrid broadcast-broadband TV (Hybrid Broadcast Broadband TV - HbbTV). The architecture of HbbTV system is given, the principle of its operation, as well as an overview of HbbTV specification standards that are in use, with their basic characteristics. Here are described the services provided by Hybrid TV. It is also provided an overview of the distribution of HbbTV services in Europe in terms of the number of TV channels that HbbTV services offer, the number of active hybrid TV devices, HbbTV standards which are in use and models of broadcast networks used to distribute HbbTV service.